PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PT. HERO SUPERMARKET TBK. CABANG GIANT EKSTRA METROPOLITAN CITY PANAM PEKANBARU - Rahmat, Yogie (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This research conducted in PT. Hero Supermarket TBK. Branch Giant Ekstra Metropolitan City Panam Pekanbaru. This research was conducted to determine the effect of service quality on customer satisfaction PT. Hero Supermarket TBK. Branch Giant Ekstra Metropolitan City Panam Pekanbaru. The population of this study is consumer PT. Hero Supermarket TBK. Branch Giant Ekstra Metropolitan City Panam Pekanbaru which amounts to 790.509. The sample in this study amounted to 100 respondents using the Slovin formula. In analyzing the data obtained from this study the authors used quantitative descriptive analysis method with simple linear regression. From the results of the t test obtained value for the variable Service Quality of 5.688 > t table is equal to 1.984. with a significant amount of 0,000 smaller than 0.05, the results of this study indicate service quality affects customer satisfaction. Based on the calculation of the determination coefficient (R2) of 0.248 or 24.8% which shows the contribution of influence given the variable quality of service to the variable customer satisfaction PT. Hero Supermarket TBK. Branch Giant Ekstra Metropolitan City Panam Pekanbaru, while the remaining 75.2% is influenced by other variables